ANALISIS HASIL PENGUJIAN DAN PREDIKSI TEORITIS AERODINAMIKA ROKET RX 300 - Ginting, Salam (BRIN Publishing, 2007)
LAPAN has a supersonic wind tunnel facility which could be used for research of rocket model to get aerodynamics characteristic of the model through testing with various speeds within supersonic range. The research on the RX 300 rocket model has been carried out in the above facility at velocity range of 1,5-3 Mach. Some aerodinamic are obtained from this research. Such as lift drag and moment ceofficients. Aerodynamic coefficient is shown in the curve as a function of Mach and angle of attack. This result will be compared with the theoretical calculation and the result is higher around 5 percent than theory. The approach of Quadrature Multhopp is method use in this analysis. The RX 300 rocket model is equipped with foru flaps at the back part of the rocket as a stabilizer when the rocket is launched. This rocket is designed for being able to carry a payload with dimention of 25 cm diameter and 45 cm length. Keywords: Aerodynamic rocket, Wind tunnel.